BIAS, INTOLERANT THINKING, AND THE AUTHORITARIAN PERSONALITY - Nasser Hussein Nasser (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research aims to identify -Prejudice and intellectual rigidity among university students. -The differences in intellectual prejudice and intolerance according to the variables: gender, specialization. -The authoritarian personality of university students. -The nature of the relationship between intellectual bias, intellectual intolerance, and the authoritarian personality, and the extent of the contribution of the authoritarian personality to intellectual bias and intellectual intolerance. The research sample consisted of (400) students from Al-Muthanna University, for the academic year (2020-2019). Intellectual bias, intellectual intolerance and authoritarian personality according to the two variables: gender (male, female), and academic specialization (scientific, humanitarian). The research also found a correlation between intellectual bias, intellectual intolerance and the authoritarian personality, and the contribution of bias and intellectual rigidity to the authoritarian personality, and based on this Results, the researcher put forward some recommendations and proposals.